Pengaruh Kepercayaan dan Kepemimpinan Transformasional Terhadap Akuntabilitas Laporan Keuangan Pondok Pesantren Al Husna - Dela Alfani; Hendra Harmain; Rahmi Syahriza (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
This study aims to determine the effect of trust and transformational leadership on the financial report accountability of Al Husna Islamic boarding school partially and simultaneously. This study uses quantitative methods with descriptive statistical analysis patterns and inferential statistics. The population in this study were all employees of the Al Husna Islamic boarding school, totaling 45 people using a sampling technique, namely Saturated Sampling. Sources of data used are primary data and secondary data. Data collection techniques using the questionnaire method (questionnaire). While the data analysis techniques used are validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, regression analysis test, and hypothesis testing. This study shows that the variables of trust and transformational leadership have a positive and significant effect on the accountability of Islamic boarding schools. So it can be concluded that the better the trust and performance of the leader in managing the Islamic boarding school, the better the accountability of the financial reports of the Al Husna Islamic boarding school seen from its financial reports.